Natural biocides for mitigation of sulphate reducing bacteria - Salwani, Md Zain; Nor Insyirah, Hairul Salleh; Arman, Abdullah (Hindawi Limited, 2018)
This study addresses the potential usage of various herbaceous plants extract including betel leave extract (BLE), green tea (GTE), turmeric (TE), belalai gajah (BGE), garlic extracts (GE), and manjakani extracts (ME) as future biocides of SRB that are natural and nontoxic. Study revealed that retardation of growth was obtained after addition of 5mL of natural biocides to 100 mL of the culture. Reduced biomass growth was observed with most of the tested biocides, dictated by lower biomass contents accepts for ginger and garlic. The planktonic growth was successively suppressed with addition of GTE, TE, and BGE, where the biomass production was decreased by more than 80.0% compared to the control experiments. GRE increased the growth of planktonic bacteria while the GE induced the formation of biofilms, showed by increase in biomass productions with over 23.4% and 77.46% enhancements, respectively. These results suggest that turmeric, green tea, and belalai gajah plants extracts are highly potential biocidal agents for mitigating SRB, thus controlling the effect of MIC on metal surfaces. However, the chemical stability, potential toxicity, and consistent performance of the extracts need further investigation for optimization of its use on a real field scale.